DIFFERENT CONCEPTS OF CYBORGS IN KAZUO ISHIGURO’S KLARA AND THE SUN - Apriliani, Defina Dwi; Alivin, Mohammad Zaimil (PARADIGM: Journal of Language and Literary Studies, 2024)
This study aims to find the difference between the representation of Klara's character and the concept of Cyborg Manifesto by Donna Haraway in the novel Klara and the Sun by Kazuo Ishiguro. This research discusses how Klara engages in the traditional organic family concept without an Oedipal project, without psychological dynamics such as conflict or emotional dependence on parental figures as in humans. It also explores how Klara remains respected despite having no awareness or understanding of the cosmos, a spiritual or philosophical perspective on the universe that is often the basis of human existence. The approaches used are posthumanism and cyborg theory, which highlight the boundary between humans and machines. The results showed important differences in the representation of Klara. This paper finds that Klara, although a cyborg, was able to form deep emotional bonds with humans and was respected for her ability. This is contrary to Haraway's concept that cyborgs are not bound by family structures and are not rewarded for their connection to the environment or cosmos. This analysis contributes to enriching the study of human-technology relations and identity dynamics in the context of posthumanism.